Situations Grammarians From The Mental Analogy - الدّيكي, محمود; العظامات, ثروت عجرم سالم (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Mental analogy is considered as one of the approved principles in rationing the theory of syntax and morphology, Mental analogy is so important since it generates many syntactic and morphological rules that have no evidence or presence in different texts. For this Study shed Light On Situation Grammarians From The Mental Analogy, Intended to highlight The Role Of Mental analogy Build attention Of Grammarians, And disclosure The most important criteria Which Grammarians Judge In this type Of Analogy .